2017
DOI: 10.4103/1735-5362.202449
|View full text |Cite
|
Sign up to set email alerts
|

Poly (ethylene-co-vinyl alcohol)-based polymeric thermo-responsive nanocarriers for controlled delivery of epirubicin to hepatocellular carcinoma

Abstract: In this study, poly(ethylene-co-vinyl alcohol) (EVOH) as a novel biocompatible polymeric scaffold was surface modified by succinylation to get EVOHS and further pegylated to improve structural properties using methoxypolyethylene glycol (5000 Da) succinate (PEGS) along with targeting with retinoic acid (RA) to get final modified active and passive targeted conjugate (PEGS-EVOHS-RA) to evaluate its ability in carrying and delivery of epirubicin to hepatocellular carcinoma cell lines in response to varying tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…A p value < 0.05 was considered significant. (Hassanzadeh et al, 2017;Mahajan and Mahajan, 2016). Furthermore, the smaller particle size of nanocarriers ensures efficient incorporation into droplets during aerosol generation (Amini et al, 2014;Dandekar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A p value < 0.05 was considered significant. (Hassanzadeh et al, 2017;Mahajan and Mahajan, 2016). Furthermore, the smaller particle size of nanocarriers ensures efficient incorporation into droplets during aerosol generation (Amini et al, 2014;Dandekar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This copolymer is synthesized by the polymerization of ethylene with vinyl acetate giving the poly(ethylene-co-vinyl acetate) following the hydrolysis of functional groups. E-VAL is also biodegradable [17], biocompatible [18][19][20][21], and possesses excellent mechanical and gas barrier properties. Few investigations have been reported on the application of this copolymer in the biomedical domain.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumura et al [20] demonstrated the control of the differentiation and proliferation of the periodontal cells used to develop a highly organized hybrid implant. Hassanzadeh et al [21] reported on the surface modification of E-VAL by succinylation to obtain succinate modified E-VAL (EVOHS) to improve the structural properties and evaluated its ability to deliver epirubicin to hepatocellular carcinoma cells in response to varying temperature. They revealed that all the characteristic properties improved as the hydrophilicity of micelles increased, and these entities can be effective as thermo responsive delivery systems for targeting the delivery of cytotoxic agents to hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…As one can see from Figure 2A, the spectrum of uncovered CFAR‐LT membrane presents all characteristic PU bonds, namely the symmetric N‐H stretching vibrations of the urethane groups near 3313 cm −1 ; the in‐plane N–H bending vibration of the isocyanate segments at 1593 cm −1 ; the stretching vibration of the carbonate groups C=O and the asymmetric stretching vibration of C–O (from N–CO–O) at 1741 and 1251 cm −1 , respectively; the C‐O‐C bond stretching vibration in the urethane group at 970 cm −1 5,13,34. The absorption peak at around 1635 cm −1 corresponds to the bonded carbonyl group 5,24,35 and indicates that a diamine was used as the chain extender in this case. A better phase separation of the hard and soft segments in case of CFAR‐LT testifies to a higher mobility of the macromolecular chains, thus promoting the diffusion of the small molecular species 13 .…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that EVOH is a biocompatible material 9,20 . For example, Hassanzadeh et al show that polymer micelles based on EVOH modified by succinylation and further pegylated can be successfully used for the epirubicin delivery for the treatment of hepatocellular carcinoma 24 . The toxicity of such modified micelles was tested on HepG2 human hepatocellular carcinoma cell line using 3‐[4,5‐dimethylthriazol‐2‐yl]‐2,5‐diphenyl tetrazolium bromide assay as a function of temperature (up to 45°C).…”
Section: Introductionmentioning
confidence: 99%